2023
DOI: 10.3389/fpsyt.2023.1074217
|View full text |Cite
|
Sign up to set email alerts
|

Unsociability and social adjustment of Chinese preschool migrant children: The moderating role of resilience

Abstract: ObjectivesThe present study examined the moderating effect of children’s resilience on the relations between unsociability and social adjustment (i.e., prosocial behaviors, peer exclusion, interpersonal skills, internalizing problems) in Chinese preschool migrant children.MethodsParticipants were N = 148 children (82 boys, Mage = 62.32 months, SD = 6.76) attending two public kindergartens in Shanghai, People’s Republic of China. Mothers provided ratings of children’s unsociability and resilience; teachers asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 67 publications
(97 reference statements)
1
2
0
Order By: Relevance
“…The present meta-analysis found significant and positive associations between unsociability and peer problems in Chinese children and adolescents, which is consistent with previous empirical findings in Chinese culture [44,46,[48][49][50]58]. Compared to the cross-cultural meta-analysis regarding the associations between social withdrawal and peer problems [51], the strength of the correlation coefficient was higher in the present study.…”
Section: Overall Associations Between Unsociability and Peer Problems...supporting
confidence: 91%
See 2 more Smart Citations
“…The present meta-analysis found significant and positive associations between unsociability and peer problems in Chinese children and adolescents, which is consistent with previous empirical findings in Chinese culture [44,46,[48][49][50]58]. Compared to the cross-cultural meta-analysis regarding the associations between social withdrawal and peer problems [51], the strength of the correlation coefficient was higher in the present study.…”
Section: Overall Associations Between Unsociability and Peer Problems...supporting
confidence: 91%
“…Although previous studies found the positive associations between unsociability and peer problems in Chinese culture [48][49][50], the strength and direction of these associations were mixed and no study has synthesized the previous findings to examine the associations in Chinese sample. Ran and colleagues conducted a meta-analysis to assess the associations between three subtypes of social withdrawal and peer problems in Chinese and North American youth to detect the mixed results in Western countries and China [51].…”
Section: The Present Studymentioning
confidence: 96%
See 1 more Smart Citation